Aerococcus viridans Native Valve Endocarditis - Wenwan Zhou; Vanessa Nanci; Andreanne Jean; Amir H Salehi; Fahad Altuwaijri; Renzo Cecere; Jacques Genest (Canadian Journal of Infectious Diseases and Medical Microbiology)
Aerococcus viridans is an infrequent human pathogen and few cases of infective endocarditis have been reported. A case involving a 69-year-old man with colon cancer and hemicolectomy 14 years previously, without recurrence, is reported. A diagnosis of native mitral valve endocarditis was established on the basis of clinical presentation, characteristic echocardiographic findings and pathological specimen examination after urgent valve replacement. A viridans endocarditis appears to be particularly virulent, requiring a surgical approach in four of 10 cases reported and death in one of nine. Given the aggressive nature of A viridans endocarditis and the variable time to diagnosis (a few days to seven months), prompt recognition of symptoms and echocardiography, in addition to blood cultures, should be performed when symptoms persist.